Sports Tourism Is A Method of Developing General Endurance In High School Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the article is devoted to a comprehensive study of the impact of sports tourism on the development of general endurance in children of secondary school age. The special importance of endurance for human life, as well as the use of sports tourism as a method of increasing physical endurance, was determined and justified. The analysis of modern methodological literature showed that there are almost no specific recommendations for developing and increasing endurance in sports tourism, as a result of which a set of author's exercises was developed to control the level of endurance used in training and research.